Analyzing the pragmatic structure of dialogues. (April 2017) - Macagno, Fabrizio; Bigi, Sarah
In this article, we describe the notion of dialogue move intended as the minimal unit for the analysis of dialogues. We propose an approach to discourse analysis based on the pragmatic idea that the joint dialogical intentions are also co-constructed through the individual moves and the higher-order communicative intentions that the interlocutors pursue. In this view, our goal is to bring to light the pragmatic structure of a dialogue as a complex net of dialogical goals (such as persuasion, deliberation, information-sharing, etc.), which represent the communicative purposes that the interlocutors intend to achieve through their utterances. Dialogue moves are shown to represent the necessary interpretive link between the general description of the dialogical context or type and the syntactical analysis of the sentences expressed by the individual utterances. In the concluding part of this article, we show how this method can be used and further developed for analyzing various types of real-life dialogues, outlining possible uses and lines of empirical research based thereon.